Blood protozoa findings in pet dogs screened in Ipoh, Malaysia - Omar, Jamnah; Panchadcharam, Chandrawathani; Bathmanaban, Premaalatha; Che Mamat, Zaini @ Zainudin; S. I., Sheikh Abdul Muizz; Jegathesuran, Tharshini; Hassan, Mohd Naheed (Department of Veterinary Services Malaysia, 2016)
A total of 103 blood samples from pet dogs around Ipoh were screened for common blood protozoa. A total of 14 samples were found positive for Erhlichia canis and one sample was found positive for microfilaria of Dirofilaria immitis. Both these diseases are transmitted by vectors; ticks (Rhipicephalus sangiuneus) and mosquitoes respectively. In the hot and wet tropical environment where vectors are abundant, pet care, hygiene and regular screening will help veterinarians detect these infections early to facilitate treatment.